A novel fluorescent surfactant enhances the delivery of the Cas9 ribonucleoprotein and enables the identification of edited cells. Issue 31 (1st April 2019) - Li, Jie; Røise, Joachim Justad; Zhang, Jingtuo; Yang, Jiaying; Kerr, D. Lucas; Han, Hesong; Murthy, Niren
Abstract : A novel fluorescent single tailed surfactant was synthesized, which can disrupt endosomes, complex lipofectamine, and identify transfected cells. Abstract : In this report, we designed and synthesized a novel fluorescent single tailed surfactant (termed FEDS), which can disrupt endosomes, complex lipofectamine, and can also identify cells that have been transfected. FEDS was able to increase the gene editing efficiency of lipofectamine/Cas9 ribonucleoprotein by 300% via a combination of fluorescent based enrichment and endosomal disruption.